(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Stability profiling is a critical aspect of pharmaceutical development, ensuring that solid dosage forms maintain quality, efficacy, and safety throughout their shelf life. Accelerated and real-time stability studies, combined with kinetic modeling, provide a scientific basis for predicting shelf life and supporting regulatory compliance. Objective: This study aimed to evaluate the stability of a representative solid dosage form under accelerated (40 °C ± 2 °C/75% RH ± 5%) and real-time (25 °C ± 2 °C/60% RH ± 5%) conditions, assessing physical, chemical, and dissolution parameters, and to predict shelf life using kinetic models. Methods: Tablets were stored under real-time and accelerated conditions for 12 months and 6 months, respectively. Periodic evaluations included appearance, hardness, friability, disintegration, assay, dissolution, and degradation-product analysis. Degradation kinetics were analyzed using zero-order, first-order, and Arrhenius models to estimate shelf life. Results: Tablets remained physically and chemically stable under real-time conditions, with assay above 98% and dissolution above 96%. Accelerated conditions caused minor physical changes and reduced assay to 94.5% over six months. Kinetic modeling indicated a predicted shelf life of 24–32 months. Conclusion: Combining real-time and accelerated stability studies with kinetic modeling provides a reliable framework for predicting the shelf life of solid dosage forms, ensuring product quality and regulatory compliance.